A little history of literature - Sutherland, John, 1938- (Little histories (Yale University Press), 2013)
From The Epic of Gilgamesh to Harry Potter, this rollicking romp through the world of literature reveals how writings from all over the world can transport us and help us to make sense of what it means to be human.